A tetrameric praseodymium substituted arsenotungstate (III) – Synthesis & characterization, electrochemistry, catalytic and its magnetic applications. (1st April 2022) - Kaushik, Reetam; Khan, Imran; Das, Vivek; Hussain, Firasat; Manabe, Jun; Nishihara, Sadafumi; Teillout, Anne-Lucie; Mbomekallé, Israël-Martyr; de Oliveira, Pedro
Graphical abstract: A new tetrameric praseodymium-substituted lone pair containing arsenotungstate has been synthesized under mild reaction conditions. The complex has been characterized by various analytical techniques and was utilized for the investigation of magnetic activity and catalytic activity for the oxidation of thioethers. Abstract: A praseodymium-substituted lone pair containing arsenotungstate with the formula Na28 [Pr4 As2 O6 (OH)2 (WO)(WO3 )2 (AsW9 O33 )4 ].70H2 O has been synthesized under mild reaction conditions. The compound was isolated in 1 M NaCl solution with the trilacunary AsW9 O33 precursor along with the addition of sodium dihydrogen phosphate during the reaction procedure. Here, the addition of the phosphorus salt played an important role in the synthetic procedure. The polyanion was characterized by various analytical techniques such as Fourier-Transform Infrared spectroscopy (FT-IR), Single Crystal X-Ray Diffraction (SC-XRD), Powder X-ray diffraction (P-XRD), Thermogravimetric Analysis (TGA), Elemental analysis (ICP-AES) and Cyclic voltammetry (CV). The catalytic activity of the polyanion was studied for thioether oxidation as a heterogeneous catalyst. The magnetic properties of the complex were also investigated.